2018
DOI: 10.1186/s13046-018-0959-0
|View full text |Cite
|
Sign up to set email alerts
|

The natural polyphenol curcumin induces apoptosis by suppressing STAT3 signaling in esophageal squamous cell carcinoma

Abstract: BackgroundWe and others have previously shown that the STAT3 signaling pathway is activated in some esophageal squamous cell carcinoma (ESCC) cells and is required for the survival and growth of these primary ESCC-derived xenografts. It has also been shown that the natural polyphenol curcumin is an effective anti-tumor agent.MethodsLuciferase assay and immunoblotting were performed to examine whether curcumin suppressed STAT3 signaling. CCK-8 assay and xenografts were utilized for analyzing ESCC cell growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…Napabucasin has been demonstrated to sensitize tumor cells to checkpoint inhibition and it has been linked to high tumor infiltration of CD8 + T cells in mice bearing 4T1 mammary tumors [217], with similar results being reported in mesothelioma [218]. Notably, curcumin has demonstrated potent anti-STAT3 activity through STAT3 cysteine modification that prevents phosphorylation and it has been found to inhibit proliferation breast cancer [219] and esophageal squamous cell carcinoma [220], with the latter being associated with significant decreases in IL-6. However, while numerous studies using mice models have reported increases in TME infiltration by T cells, suppression of Tregs and MDSCs, and decreased NFκB signaling [221] in tumor bearing animals, curcumin has also been linked to the inhibition of DC activation [222,223].…”
Section: Therapeutic Modulation Of Statsmentioning
confidence: 79%
“…Napabucasin has been demonstrated to sensitize tumor cells to checkpoint inhibition and it has been linked to high tumor infiltration of CD8 + T cells in mice bearing 4T1 mammary tumors [217], with similar results being reported in mesothelioma [218]. Notably, curcumin has demonstrated potent anti-STAT3 activity through STAT3 cysteine modification that prevents phosphorylation and it has been found to inhibit proliferation breast cancer [219] and esophageal squamous cell carcinoma [220], with the latter being associated with significant decreases in IL-6. However, while numerous studies using mice models have reported increases in TME infiltration by T cells, suppression of Tregs and MDSCs, and decreased NFκB signaling [221] in tumor bearing animals, curcumin has also been linked to the inhibition of DC activation [222,223].…”
Section: Therapeutic Modulation Of Statsmentioning
confidence: 79%
“…2) is a polyphenol compound extracted mainly from the rhizomes of Curcuma longa, Curcuma zedoaria and Acorus calamus L. with many biological activities, but it has poor water solubility and stability [11]. Clinical evidence and extensive studies showed that curcumin has various pharmacology effects, including anti-cancer, anti-inflammatory, and anti-oxidative activities [12][13][14]. Curcumin and its analogues are shown to be emerging as effective agents for the treatment of several malignant diseases such as cancer.…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin inhibits cell growth, induces cell cycle arrest and apoptosis in esophageal squamous cell carcinoma EC1, EC9706, KYSE450, TE13 cells through STAT3 activation [12]. It also induces oxidative stress, which disrupts the mitochondrial membrane potential and causes the release of cytochrome c, thus inducing apoptosis [26].…”
Section: Curcuminmentioning
confidence: 99%
“…To determine the mRNA levels of USP44, qRT‐PCR was performed by using SYBR Green qPCR Master Mix (Clontech Laboratories, Inc., Fitchburg, WI) as described previously . The primers used were as follows: USP44, forward 5′‐ ACAACTTATGATATGCCACC ‐3′ and reverse 5′‐ GATTTCCTCAAAGCCAAC ‐3′; GAPDH, forward 5′‐ GCACCGTCAAGGCTGAGAAC ‐3′ and reverse 5′‐ TGGTGAAGACGCCAGTGGA‐ 3′.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the mRNA levels of USP44, qRT-PCR was performed by using SYBR Green qPCR Master Mix (Clontech Laboratories, Inc., Fitchburg, WI) as described previously. 15 The primers used were as follows:…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%